PELATIHAN PENGOLAHAN FESES DAN URINE SAPI MENJADI PUPUK ORGANIK RAMAH LINGKUNGAN SEBAGAI UPAYA PENINGKATAN PRODUKTIVITAS PERTANIAN - Widijanto, Hery; Omar Danendra, Diego; Violeta Putri, Aisya; Apriani, Devi (Inisiasi, 2024)
The need for environmentally friendly organic fertilizers is increasing with the awareness of the negative effects of using chemical fertilizers in the long run. Ngancar Village, located in Giriwoyo Sub-district, Wonogiri Regency, is one of the areas with great potential in agriculture and livestock, as there are a large number of farmers who also raise livestock in the area. Livestock rearing in Ngancar Village is generally inadequate and has not yet processed waste in the form of solid waste (feces) and liquid waste (urine). The people of Ngancar Village are generally unaware of the processing technology and the benefits of proper management of livestock waste. The purpose of this activity is to provide the community with the knowledge and skills to process cow dung and urine into environmentally friendly organic fertilizer in Ngancar Village. The methods used include coordination with village officials and farmer groups, land surveys, socialization of organic fertilizer production, support and fertilizer production. As a result of these activities, the community has the knowledge and skills to process cow urine and dung waste into liquid and solid organic fertilizers for sustainable agriculture. The community also has the mindset to process and utilize existing local wastes and potentials into useful and economically valuable products.